Selective C–Si Bond Formation through C–H Functionalization - Sharma, Ritika; Kumar, Rakesh; Kumar, Inder; Singh, Bikram; Sharma, Upendra (Synthesis, 2015)
Silylation of hydrocarbons is one of the most important transformations due to the diverse application of organosilanes. Continuous progress is being made in organosilane synthesis particularly through direct C–H activation/functionalization. This minireview compiles various processes reported for C–Si bond formation from 2000–2014, through C–H activation/functionalization (proximal and remote) and metal-free approaches.1 Introduction2 C–Si Bond Formation through C–H Activation in Intermolecular Fashion2.1 C–Si Bond Formation through Direct C(sp2)–H Activation2.2 C–Si Bond Formation through Directing Group Assisted C(sp2)–H Activation2.3 C–Si Bond Formation through sp3 C–H Activation3 C–Si Bond Formation through Proximal C–H Activation/Functionalization in Intramolecular Fashion3.1 Intramolecular C–Si Bond Formation through C(sp2)–H Activation3.2 Intramolecular C–Si Bond Formation through C(sp3)–H Activation4 Siloles Synthesis through Heteroannulation5 C–Si Bond Formation through Remote C–H Activation6 C–Si Bond Formation through C–O Bond Cleavage7 Metal-Free Methods for C–Si Bond Formation8 Summary and Outlook
Keywords: silylation; C–H activation; catalytic; metal-free; siloles